The universe : from flat earth to black holes--and beyond - Asimov, Isaac, 1920-1992. (New York : Walker, 1980)
Presents a scientific survey of what is known about the universe. Includes black holes, white holes, optical quasars and theories on the extent of the universe.
Includes index.
Bibliography: p. 307.
Booklist.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Astronomy -- Popular works; Astronomy; Universe